Implementasi Program Adiwiyata Terhadap Karakter Peduli Lingkungan di SD Inpres Ta’binjai Kabupaten Gowa - Ashar Ashar; Ainun Jariah; Nurwahidah Nurwahidah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The objective of this research is to describe the implementation of the Adiwiyata program in fostering environmental care characters at SD Inpres Ta'binjai, Bontonompo District, Gowa Regency. The study aims to serve as an evaluative tool for Adiwiyata schools regarding environmental care characters that still need improvement within the school environment. Employing a qualitative descriptive method, data collection techniques encompass interviews, observations, and documentation. Data analysis involves data reduction, presentation, and drawing conclusions. The findings reveal that the implementation of the Adiwiyata program in shaping environmental care characters among students at SD Inpres Ta'binjai has been effectively executed. The school has integrated its policies into its vision and mission. Environmental education activities are participatory, involving all school elements—teachers, staff, and students. Noteworthy environmental facilities include accessible sinks in each classroom, eliminating the need to travel to distant bathrooms, and medicinal plants on campus for student health. The implementation showcases outstanding and agile initiatives such as green campaigns and health campaigns. Overall, the research underscores the successful integration of the Adiwiyata program in nurturing environmental care characters among students at SD Inpres Ta'binjai, Bontonompo District, Gowa Regency, with commendable environmental initiatives and facilities.